(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2023)
Dasatinib, a potent oral multi-targeted kinase inhibitor against Src and Bcr-Abl, can decrease inflammatory response in sepsis. A simple and cost-effective method for determination of an effective dose dasatinib was established. This method was validated in human plasma, with the aim of reducing the number of animals used, thus, avoiding ethical problems. Dasatinib and internal standard lopinavir were extracted from 180 uL of plasma using liquid-liquid extraction with methyl tert-butil ether, followed by liquid chromatography coupled to triple quadrupole mass spectrometry in multiple reaction monitoring mode. For the pharmacokinetic study, 1 mg/kg of dasatinib was administered to mice with and without sepsis. The method was linear over the concentration range of 1-98 ng/mL for DAS in mice and human plasma, with r2>0.99 and presented intra- and interday precision within the range of 2.3 - 6.2 and 4.3 - 7.0%, respectively. Further intra- and interday accuracy was within the range of 88.2 - 105.8 and 90.6 - 101.7%, respectively. The mice with sepsis showed AUC0-t = 2076.06 h*ng/mL and Cmax =102.73 ng/mL and mice without sepsis presented AUC0-t = 2128.46 h*ng/mL. Cmax = 164.5 ng/mL. The described analytical method was successfully employed in pharmacokinetic study of DAS in mice.